Synthesis, Characterization, X-Ray Crystal Structure, and Antimicrobial Activity of 1,1′-(3,4-Diphenylthieno[2,3-b]thiophene-2,5-diyl)diethanone - Yahia Nasser Mabkhot; Fahad D. Aldawsari; S. S. Al-Showiman; Assem Barakat; M. Iqbal Choudhary; Sammer Yousuf (Journal of Chemistry)
Synthesis of 1,1′-(3,4-diphenylthieno[2,3-b]thiophene-2,5-diyl)diethanone (4) is reported here. The structure of compound 4 was deduced by 1H-NMR, 13C-NMR, FT-IR, MS, microanalysis, and single-crystal X-ray diffraction. Compound crystallizes in the monoclinic space group P21/n with a = 9.3126(7) Å, b = 9.5867(7) Å, c = 20.2811(15) Å, α = 90°, β = 95.436(2)°, γ = 90°, V = 1802.5(2) Å3, and Z = 4. The molecules are packed in crystal structure by weak intermolecular C10–H10A⋯ S1 hydrogen bonding interactions. Compound 4 can be a useful intermediate for the synthesis of diphenylthieno[2,3-b]thiophene. Compound 4 was found to be active against Gram-positive bacteria (Bacillus subtilis and Staphylococcus pneumoniae) and Gram-negative bacteria (Escherichia coli) and also was found to be active against fungi (Aspergillus fumigatus and Candida albicans).